Sustainable approach for galvanic waste processing by energy-saving ferritization with AC-magnetic field activation. Issue 1 (31st December 2022) - Samchenko, Dmitry; Kochetov, Gennadii; Derecha, Dmytro O.; Skirta, Yurii B.
Abstract: The efficiency of the AC-magnetic field usage for resource-saving activation of the reaction mixture in the ferritization process with the extraction of heavy metals ions from galvanic waste has been confirmed. The one of the key parameters of the ferritization process—the ratio of the concentration of iron ions to the total concentration of other metal ions on the quality of galvanic waste processing has been investigated. It is determined that under the optimal processing conditions (ratio of concentrations of iron ions to other heavy metal ions 3.5 ÷ 4/1) the residual concentrations of heavy metal ions decrease to the values: Fe 2+;3+ —0, 1; Ni 2 +— 0.26; Cu 2 + —0.2; Zn 2 + —0.19 mg/dm 3 . It is established that the AC-magnetic field activation provides the metal ions extraction degree of 99.96%, and also has undeniable energy advantages in comparison with thermal technique: the energy consumption is reduced by more than 60%. This indicates the suitability of purified water for reuse in galvanic production due to the requirements for the heavy metal ions content. Also, the structural studies of ferritic sediments shown that samples obtained at the ratio of heavy metal ions concentrations 4/1 phases characterized by the maximum content of crystalline ferromagnetic ferrite (Ni0.53 Cu0.3 Zn0.17 Fe2 O4 ) ≥ 76% were detected.